Molecular diagnosis of oral pre-malignant lesions & oral squamous cell carcinoma in saliva-A breakthrough in Pakistan. - Iqbal A. Muhammad Khyani; Qureshi, Masood A.; Farooq, M. Umar; Mirza, Talat (International Journal of Endorsing Health Science Research, 2014)
Objective: To evaluate salivary detection of interleukin 6 & 8 and high risk HPV-16 & 18 are informative biomarkers of Oral Pre-malignant Lesion (PML) and Oral Squamous Cell Carcinoma (OSCC) in our population. Duration: July 2011 to December 2012. Subjects and Methods: Total 105 cases were included. The subjects were divided in three groups ‘A’, ‘B’ & ‘C’ having 35 participants each. Group ‘A’ comprised of patients having strong clinical evidence of oral PML. Group ‘B’ constitutes histologically proven OSCC and Group ‘C’ includes disease free subjects as controls. Relevant clinical history was recorded after informed consent on institutional approved performa. Saliva was collected as per standard drooling method’. Samples were stored at +4oC and later transferred to Dow Diagnostic, Research & Reference Laboratory to store it at -20oC before further process. Samples were subjected to centrifugation at 4500 rpm for 15 minutes at 4oC. Supernatant fluid phase was used in ELISA for detection and uantification of IL6 and IL8. Cell pellets were used for identification of high risk HPV-16 & 18 by real-time PCR. Data was entered and analyzed on SPSS version 16. P-value of 0.05 was taken as standard reference. Results: In group ‘A’, IL6 was not detected in almost all the subjects except one case. IL8 was detected in 26/35 (74.3%) subjects and not detected in 09 (25.7%) cases. In group ‘B’, IL6 was detected in 13 (37.1%) cases and in 22 (62.9%) cases, it cannot be detected. IL8 was detected in 33 (94.3%) and it was not detected in 02 (5.7%) subjects. It is observed that IL8 is consistently found raised in group ‘A’ & ‘B’. In group ‘C’, IL6 was not detected in any of the subject while IL8 was detected in 10(28.6%) cases. Significant association was found for qualitative salivary detection of IL6 and IL8 between the groups (P= < 0.0001 and < 0.0001 respectively). Regarding quantitative salivary concentration of IL6 & IL8, no significant co-relation was found in salivary levels of IL6 between the groups while there was significant association of salivary IL8 levels between the groups (P= <0.0001). On post Hoc multiple comparison, significant co-relation was found in IL8 levels between oral PML group and controls (P=0.001) and OSCC group and controls (P= <0.0001). In group ‘A’, HPV-16 was detected in salivary samples of 3 (8.6%) cases while HPV-18 was not detected. In group ‘B’, HPV-16 was detected in the salivary samples of 07 (20%) cases while HPV-18 was detected in 06 (17.1%) cases. Mixed HPV-16 and HPV-18 were found in 02 (5.7%) cases. In group ‘C’, HPV-16 was detected in 03(8.6%) cases while HPV-18 was not detected in any of the subjects. Significant relationship was observed between the groups for salivary HPV-18 detection (P= 0.002) while for detection of HPV-16, no significant association was found (P= 0.245). Conclusion: Salivary concentration of IL6 and IL8 in oral PML and oral cancer are useful biomarkers in our population. Detection of HPV infection for the causation of oral cancer cannot be fully established possibly due to small sample size. Moreover different genetic makeup, environmental and geographic differences, indulgence in peculiar risk factor habits and different sexual practices compared to west due to socio-cultural and religious restrictions could be the reason.